Central bank money as a catalyst for fungibility: The case of stablecoins - Charles-Enguerrand Coste; George Pantelopoulos (European Central Bank (ECB), 2025)
To ensure that means of payments are readily interchangeable at face value - i.e. fungible - for retail payments, three elements are required: (1) settlement finality; (2) interoperability; and (3) seamless convertibility of the means of payment into the "ultimate" or quasi-ultimate means of payment. This paper argues that stablecoins issued by different issuers on different blockchains can be fungible to the same extent as commercial bank deposits from different banks provided that (i) payment and settlement technologies are interoperable, (ii) payments are transacted on ledgers that offer settlement finality, and (iii) that central bank money acts as the anchor to the monetary system (assuming that the central bank money is itself underscored by a homogenous unit of account). On this basis, this paper asserts that tokenised funds and off-chain collateralised stablecoins are fungible means of payments under some conditions, and that on-chain collateralised stablecoins can be prima facie classified as fungible means of payments, so long as the identical preconditions associated with accomplishing means of payment fungibility for tokenised funds/off-chain collateralised stablecoins can be fulfilled, and on the premise that the on-chain collateral can be readily converted into higher level money. Finally, it is determined that algorithmic stablecoins are not fungible means of payments.
Keywords: B26; E42; 330; stablecoin; electronic money token; fungibility; central bank